2015
DOI: 10.1016/j.rbmo.2015.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Association between p53 Arg72Pro polymorphism and recurrent pregnancy loss: an updated systematic review and meta-analysis

Abstract: The p53 tumour suppressor gene plays an important role in angiogenesis and apoptosis. The association between Arg72Pro polymorphism and recurrent pregnancy loss (RPL) has been studied but with inconsistent results. A meta-analysis was conducted to examine whether p53 Arg72Pro polymorphism is a risk factor for RPL. Electronic searches of PubMed, Embase and Web of Knowledge were conducted to identify relevant studies. The final meta-analysis included six published articles with 730 RPL cases and 613 controls. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 29 publications
(31 reference statements)
1
13
0
Order By: Relevance
“…These results are consistent with five meta-analyses examining the relationship between p53 p.Arg72Pro variant and RPL [11,[36][37][38][39]. Tang et al, 2011 analyzed four case control studies and concluded that women with the homozygous Pro/Pro genotype had an increased risk of RPL [11].…”
Section: Discussionsupporting
confidence: 64%
“…These results are consistent with five meta-analyses examining the relationship between p53 p.Arg72Pro variant and RPL [11,[36][37][38][39]. Tang et al, 2011 analyzed four case control studies and concluded that women with the homozygous Pro/Pro genotype had an increased risk of RPL [11].…”
Section: Discussionsupporting
confidence: 64%
“…Heterogeneity was judged by calculating the I 2 statistic, where an I 2 value from 0 to 25% indicates low heterogeneity, 25-50% moderate heterogeneity and ≥50% high heterogeneity . For I 2 < 50%, a fixed effect model was chosen, and for I 2 ≥ 50%, a random effect model was chosen (Chen et al, 2015). All statistical analyses were undertaken using STATA version 12.0.…”
Section: Discussionmentioning
confidence: 99%
“…However, limited data made it necessary for us to be cautious in these studies. Chen et al [22] conducted another meta-analysis including 6 studies in 2015. There existed a significant association in allelic model (Pro vs. Arg) and recessive model (Pro/Pro vs. Arg/Pro+Arg/Arg), and subgroup analysis by ethnicity also indicated a significant association in Caucasian group.…”
Section: Discussionmentioning
confidence: 99%